2001
DOI: 10.1017/s1355838201010561
|View full text |Cite
|
Sign up to set email alerts
|

The ATP requirement for U2 snRNP addition is linked to the pre-mRNA region 5′ to the branch site

Abstract: Association of U2 snRNP with the pre-mRNA branch region is the first ATP-dependent step in spliceosome assembly. The basis of this energy dependence is not known. Previously, we identified minimal intron-derived substrates that form complexes with U2 independent of ATP. Here, we identify the intron region linked to the ATP dependence of this step by comparing these substrates to longer RNAs that recapitulate the ATP requirement. This region needed to impose ATP dependence lies immediately 59 to the branch site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…We have recently shown that hnRNP A1 inhibits the formation of the spliceosomal A complex at a step subsequent to U2AF65 binding to the polypyrimidine tract, and we speculated that hnRNP A1 binding sterically blocks the association of SF1/mBBP and/or U2 snRNP (Tange et al+, 2001)+ The primary role of the S3 for splicing inhibition provides further support for this model, as the S3 element coincides precisely with one of the major branchpoints at position Ϫ26 (T+Ø+ Tange & J+ Kjems, submitted)+ Concurrently, binding of hnRNP A1 to the S3 region probably also inhibits binding of U2 snRNP to the branchpoint at position Ϫ16 based on the finding that U2 snRNP association involves nonspecific binding of an anchoring region 6-15 nt upstream of the branchpoint (Newnham & Query, 2001)+ Binding of hnRNP A1 to other important splicing signals may also contribute to its inhibitory effect+ For instance, hnRNP A1 may interfere with binding of positive splicing factors to the GAA repeats in the ESE3 as suggested by Zhu et al+ (2001), whereas the unchanged accessibility of regions near the 39 splice site upon hnRNP A1 binding implies that the recognition of the splice site itself by the spliceosome may not be influenced by hnRNP A1+…”
Section: Hnrnp A1 Multimerizationmentioning
confidence: 89%
“…We have recently shown that hnRNP A1 inhibits the formation of the spliceosomal A complex at a step subsequent to U2AF65 binding to the polypyrimidine tract, and we speculated that hnRNP A1 binding sterically blocks the association of SF1/mBBP and/or U2 snRNP (Tange et al+, 2001)+ The primary role of the S3 for splicing inhibition provides further support for this model, as the S3 element coincides precisely with one of the major branchpoints at position Ϫ26 (T+Ø+ Tange & J+ Kjems, submitted)+ Concurrently, binding of hnRNP A1 to the S3 region probably also inhibits binding of U2 snRNP to the branchpoint at position Ϫ16 based on the finding that U2 snRNP association involves nonspecific binding of an anchoring region 6-15 nt upstream of the branchpoint (Newnham & Query, 2001)+ Binding of hnRNP A1 to other important splicing signals may also contribute to its inhibitory effect+ For instance, hnRNP A1 may interfere with binding of positive splicing factors to the GAA repeats in the ESE3 as suggested by Zhu et al+ (2001), whereas the unchanged accessibility of regions near the 39 splice site upon hnRNP A1 binding implies that the recognition of the splice site itself by the spliceosome may not be influenced by hnRNP A1+…”
Section: Hnrnp A1 Multimerizationmentioning
confidence: 89%
“…These findings should be interpreted with some caution, however, since proteins complexed with a nonhydrolyzable ATP analogue might not be fully functionally equivalent to corresponding ATP-bound forms (24). Proteins also vary in their ability to recognize and hydrolyze ATP analogs, and this could explain the difference between NS1 and the E445Q mutant in AMP-PNP experiments (43,48,64). Indeed, we could observe binding for the E445Q mutant in the presence of another nonhydrolyzable ATP analog, ATP-␥S.…”
Section: Discussionmentioning
confidence: 99%
“…3A) (30). RNA oligomers were chemically synthesized and purified as described previously (31), except for the 66-nt-long 3Ј fragment of rRNA substrate 1. The latter was transcribed in vitro and therefore required a guanosine at its 5Ј end instead of the naturally occurring cytidine.…”
Section: Methodsmentioning
confidence: 99%